Intraocular pressure, corneal thickness, and corneal hysteresis in Steinert's myotonic dystrophy - Garcia Filho,Carlos Alexandre de A. (2011)
PURPOSE: Low intraocular pressure (IOP) measured by Goldmann applanation tonometry (GAT) is one of the ocular manifestations of Steinert's myotonic dystrophy. The goal of this study was to evaluate the corneal-compensated IOP as well as corneal properties (central corneal thickness and corneal hysteresis) in patients with myotonic dystrophy. METHODS: A total of 12 eyes of 6 patients with Steinert's myotonic dystrophy (dystrophy group) and 12 eyes of 6 age-, race-, and gender-matched healthy volunteers (control group) were included in the study. GAT, Dynamic Contour Tonometry (DCT-Pascal) and Ocular Response Analyzer (ORA) were used to assess the IOP. Central corneal thickness was obtained by ultrasound pachymetry, and corneal hysteresis was analyzed using the ORA device. In light of the multiplicity of tests performed, the significance level was set at 0.01 rather than 0.05. RESULTS: The mean (standard deviation [SD]) GAT, DCT, and corneal-compensated ORA IOP in the dystrophy group were 5.4 (1.4) mmHg, 9.7 (1.5) mmHg, and 10.1 (2.6) mmHg, respectively. The mean (SD) GAT, DCT, and corneal-compensated ORA IOP in the control group was 12.6 (2.9) mmHg, 15.5 (2.7) mmHg, and 15.8 (3.4) mmHg, respectively. There were significant differences in IOP values between dystrophy and control groups obtained by GAT (mean, -7.2 mmHg; 99% confidence interval [CI], -10.5 to -3.9 mmHg; P<0.001), DCT (mean, -5.9 mmHg; 99% CI, -8.9 to -2.8 mmHg; P<0.001), and corneal-compensated ORA measurements (mean, -5.7 mmHg; 99% CI, -10.4 to -1.0 mmHg; P=0.003). The mean (SD) central corneal thickness was similar in the dystrophy (542 [31] µm) and control (537 [11] µm) groups (P=0.65). The mean (SD) corneal hysteresis in the dystrophy and control groups were 11.2 (1.5) mmHg and 9.7 (1.2) mmHg, respectively (P=0.04). CONCLUSIONS: Patients with Steinert's myotonic dystrophy showed lower Goldmann and corneal-compensated IOP in comparison with healthy individuals. Since central corneal thickness and corneal hysteresis did not differ significantly between groups, the lower IOP readings documented in this dystrophy seem not to be related to changes in corneal properties.